Digitalisasi Data Santri Pondok Pesantren Berbasis Energi Terbarukan: Integrasi Listrik Tenaga Surya dalam Manajemen Pesantren - Riyatno Riyatno; Fikra Titan Syifa; Danny Kurnianto; Khosirun Khosirun; Risang Windu Sidanti; Muhamad Zulva Ramadan; Brawijaya Brawijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Islamic boarding schools (pesantren) play a strategic role in character building and community empowerment. However, many pesantren still face challenges in managing student data using manual systems and limited access to stable electricity to support digital transformation. This community service program aimed to integrate student data digitalization with renewable energy utilization through the implementation of a Solar Home System (SHS) Box at Pondok Pesantren Wali Barokah Cipawon. The program covered the development of a digital student data management system, installation of the SHS Box as an alternative power source, and training and mentoring for pesantren administrators and students. The implementation employed a participatory approach consisting of needs assessment, system design, implementation, and monitoring and evaluation. The results show that administrative efficiency increased by 70–85%, particularly in data searching and updating processes, leading to faster access and a lower risk of data loss. From the energy perspective, the SHS Box provided an average electricity supply of 6–8 hours per day to support essential digital devices (a laptop, a smartphone, and a modem) and reduced reliance on conventional grid electricity (PLN) by approximately ±20%, with an estimated monthly electricity saving of ±10–20%. In addition, the program improved digital literacy and renewable energy awareness among students. Overall, this initiative produced a sustainable integration model of digitalization and solar energy that can be replicated in other pesantren as part of environmentally friendly and adaptive institutional management.